2019
DOI: 10.1002/slct.201901776
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Thermodynamic Properties of Metal Hydroborates

Abstract: Metal hydroborates from M(BH 4 ) n to M x (B 12 H 12 ) y currently attract a strong interest for potential applications in the field of hydrogen storage and more recently as solid ionic conductors. While thermodynamic data for the alkali borohydrides (MBH 4 ) are well known, experimental data for other compounds are cruelly lacking. Using a combination of theoretical (DFT) and experimental data, we calculate the lattice enthalpy for a series of borohydrides. The comparison with literature data show that these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…The presence of NaBr and MgBr 2 can potentially play a role, albeit minor, in the decomposition reaction of Mg­(B 3 H 8 ) 2 -MgH 2 . It has been shown that the ionic radii of Br – and BH 4 – are of similar size, making it the formation of mixed salts, such as Mg­(BH 4 ) 2– x Br x , possible during heating of Mg­(B 3 H 8 ) 2 in the presence of NaBr or MgBr 2 . Furthermore, the ionic substitution of halide for BH 4 was shown to modify the stability of metal borohydrides, specifically of NaBH 4 and LiBH 4 . , However, with our experimental data available, it is very difficult to appreciate the extent of this mixed salt formation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The presence of NaBr and MgBr 2 can potentially play a role, albeit minor, in the decomposition reaction of Mg­(B 3 H 8 ) 2 -MgH 2 . It has been shown that the ionic radii of Br – and BH 4 – are of similar size, making it the formation of mixed salts, such as Mg­(BH 4 ) 2– x Br x , possible during heating of Mg­(B 3 H 8 ) 2 in the presence of NaBr or MgBr 2 . Furthermore, the ionic substitution of halide for BH 4 was shown to modify the stability of metal borohydrides, specifically of NaBH 4 and LiBH 4 . , However, with our experimental data available, it is very difficult to appreciate the extent of this mixed salt formation.…”
Section: Resultsmentioning
confidence: 99%
“…The unsolvated Mg(B 3 H 8 ) 2 was prepared according to the procedure recently reported by Moury et al 12 The compound was analyzed by 11 B solid-state MAS NMR at 25 °C, and the chemical shifts are shown in Figure 1. The peak assignments and quantification from the − are of similar size, 45 making it the formation of mixed salts, such as Mg(BH 4 ) 2−x Br x , possible during heating of Mg(B 3 H 8 ) 2 in the presence of NaBr or MgBr 2 . Furthermore, the ionic substitution of halide for BH 4 was shown to modify the stability of metal borohydrides, specifically of NaBH 4 and LiBH 4 .…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The overall enthalpy of reaction for the dehydrogenation of Mg(BH 4 ) 2 (∆ f H • = −208 kJ/mol) to form MgB 2 (∆ f H • = −91.96 kJ/mol) and hydrogen can be calculated [45][46][47] to be equal to +116 kJ/mol, i.e., less than 30 kJ/mol per hydrogen molecule released, which is, in principle, in the correct range for a hydrogen storage material [13]. The first step of a dehydrogenation reaction of BH 4…”
Section: Magnesium Borohydridementioning
confidence: 99%
“…For alkali borohydrides, thermodynamical data are available [47], but only few other experimental data are available. Using the experimental values of the formation enthalpy of Mg(BH 4 ) 2 [45] and La(BH 4 ) 3 [63], the formation enthalpy of other M(BH 4 ) 2 and M(BH 4 ) 3 compounds were estimated, assuming that the lattice enthalpy of bromides and borohydrides with the same metal ion were identical within about 15 kJ/mol [46]. The experimental formation enthalpy of NH 4 B 3 H 8 (−530 ± 33 kJ/mol) [64], (NH 4 ) 2 B 10 H 10 (−359.2 ± 10 kJ/mol) [65], and of guanidinium and other nitrogen-based closo-borates was reported [66].…”
Section: Dft Calculationsmentioning
confidence: 99%